Why they willingly become victims of dating violence: a phenomenological study based on female adolescent perspective - Ayu, Suci Musvita; Shaluhiyah, Zahroh; Widjanarko, Bagoes; Purwanti, Ani (Intelektual Pustaka Media Utama, 2023)
Dating has become a trend in today's youth. Psychological conditions are still unstable and are one of the triggers for violence among adolescents, and in general, female adolescents become victims. However, the female adolescents maintained the relationship. Therefore, this study aimed to conduct a phenomenological study of dating violence among female adolescents. This research is included in the type of qualitative research. Data were obtained from five key informants and five triangular informants who were selected using a purposive sampling technique. Data was collected using 14 questions items submitted using the In-depth Interview technique. The interview results were transcribed using computer aided qualitative data analysis software. Based on the results of the interviews, dating is a form of self-actualization to get love and to exist among adolescents. They hope the current partner can become a life partner when they have a family. This is their reason for tolerating physical, psychological, or sexual violence perpetrated by their partner. So, female adolescents are aware that they experience violence. However, they could not avoid it because they hoped their current partner would become a life partner These results confirm the urgency for adolesence dating violence (ADV) program implementation.